Evaluating the Implementation of the School Zoning Policy in Primary School Admissions: A Case Study of Mamasa Regency - Jonson; Risma Niswaty; Herman H; Muh. Rizal S; Andi Muhammad Rivai (International Journal Of Public Policy and Bureaucracy, 2025)
This study aims to evaluate the implementation of the zoning system policy for elementary school student admissions in Mamasa Regency. Employing a qualitative approach with a descriptive-evaluative method, data were collected through in-depth interviews, direct observations, and document analysis. Informants included education office officials, school principals, teachers, parents, and community leaders. The data were analyzed using techniques of data reduction, data presentation, and conclusion drawing. The findings reveal that the zoning policy contributes positively to equitable access to education, reduces dropout rates, and improves the efficiency of educational resource allocation. The system has helped achieve a more even distribution of students across schools, particularly in densely populated areas. However, the implementation still faces several challenges. These include unequal infrastructure development between regions, limited school capacities in certain zones, resistance from parents who prefer non-zoned schools, and instances of address falsification to bypass the policy. A situational analysis further indicates that while the zoning system enhances fairness in student placement, it also exposes disparities in school quality across different zones. The study suggests that to optimize the policy’s impact, improvements should focus on upgrading educational infrastructure, ensuring equitable teacher distribution, increasing public awareness, and conducting periodic policy evaluations. Overall, the zoning policy holds potential as a strategy to promote inclusive and fair education, but its effectiveness depends on addressing systemic inequalities and enhancing local implementation capacity in Mamasa Regency.